2019
DOI: 10.1007/s10926-018-09826-x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Support and Social Integration Factors on Return to Work Outcomes for Individuals with Work-Related Injuries: A Systematic Review

Abstract: Purpose In occupational rehabilitation, the biopsychosocial model endorses the role of social factors in worker recovery. We conducted a systematic review to explore three questions examining the role of social support for the return-to-work (RTW) of individuals with work-related injury: (1) What are the worker-identified social barriers and facilitators in RTW; (2) What is the relationship between social factors and RTW; and (3) What is the effectiveness of social interventions for RTW. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 58 publications
(120 reference statements)
3
40
0
Order By: Relevance
“…A previous study showed that post-injury rehabilitation was quicker among the those reporting strong social relationships [1]. Family support may serve as a facilitator for RTW, either due to practical assistance (e.g., driving the injured worker to work or appointments) or to emotional support [38]. In the current study, the probability of married workers (with and without children) to not RTW was lower in comparison to single employees.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…A previous study showed that post-injury rehabilitation was quicker among the those reporting strong social relationships [1]. Family support may serve as a facilitator for RTW, either due to practical assistance (e.g., driving the injured worker to work or appointments) or to emotional support [38]. In the current study, the probability of married workers (with and without children) to not RTW was lower in comparison to single employees.…”
Section: Discussionmentioning
confidence: 40%
“…Multidisciplinary intervention programs focusing on RTW following an injury have proven effective [38,[45][46][47]. Such programs, which include occupational rehabilitation, social and psychological support as well as monitor the ability to RTW, have shown excellent results in reducing the expenditure of disability allowances in Sweden, Britain and Holland [48].…”
Section: Policy Implications and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compensation and income support processes operate in adversarial and scrutinising ways, and engaging in these has been shown to create stress and negatively impact mental health, functional abilities, social inclusion, and quality of life [7,8] . Receiving inadequate care or support after a workplace injury is associated with increased risk of psychosocial difficulties in returning to work [9,10] . In-terventions that act to increase individual empowerment and psychosocial wellbeing may increase resilience in engaging with needed compensatory, health and welfare systems, as well as promote quicker recovery from the workplace injury itself [7] .…”
Section: Psychosocial Issues In Workplace Injury and Rehabilitationmentioning
confidence: 99%
“…Significant others (SOs), like partners, family members or friends, can play an important role in work and health outcomes of individuals with a chronic disease [1][2][3][4]. SOs can be an important resource to help individuals cope effectively with a chronic disease and to manage their working life [1,[4][5][6], and may therefore be important facilitators of work participation.…”
Section: Introductionmentioning
confidence: 99%